MANAJEMEN MODAL KERJA DAN MENETAPKAN KEBIJAKAN KEBUTUHAN MODAL KERJA YANG SESUAI SYARIAH - Rofi'ah, Ullul Hidayati (LIPI, 2017)
Working capital is one of the most important elements in the company. Because without working capital the company can not meet the required funds to run its activities. The period of working capital turnover has since been reduced to the elements of working capital to become cash again, is less than a year or short term. The period of working capital turnover shows the level of efficiency of the use of working capital. The faster the working capital turnover the more efficient the use of working capital, and of course. Therefore, financial managers are guided to pay attention to the source of funds to fulfill the working capital. Understanding of capital in the concept of Islamic economy means all the treasures in the view syar'i, where human activities participate in business production with the aim of development. The term capital should not be limited to RIBA assets alone, and it includes all types of assets accumulated during the process of company activity and development control in other periods. Capital is called capital which means the goods produced by nature or man-made, which is necessary not to meet directly the human desire to help produce other goods that will be able to meet human needs directly and generate profits. In developing capital, to increase or increase the amount of capital with a variety of halal efforts, both through production and investment. All that can be in accordance with the desired.